Potable water quality characteristics - Salleh, Mohd. Noor; Zainudin, Zaki (Institution of Engineers Malaysia, 2011)
All living organisms on this planet are dependant on water either as a place of habitat or for drinking. Humans are not excluded from this rule, where the body, depending on size is said to consist of between 55 – 78% water. To maintain proper hydration, the human body needs approximately one to two liters of water per day, which is more or less equivalent to six glasses [1]. To cater for this need in the modern era, facilities are built to treat raw water sources before it is distributed to the general population. In Malaysia, the most tapped raw water source are rivers, which are technically under the jurisdiction of the respective state governments [2], supported by federal agencies as ascribed in the constitution. Most water treatment plants, employ conventional treatment systems, that typically consist of filtration (such as sand filtration), coagulation and flocculation, disinfection (chlorination) and flouridization. As development becomes more rampant, river water quality degradation also becomes more widepsread, consequentially broadening the spectrum of contaminants. Conventional treatment systems, at times, are not able to remove these contaminants and as a result they might enter the distribution and supply network. To manage this problem, the Environmental Quality Act, 1974, prescribes more stringent regulatory compliance for wastewater discharging premises located upstream of a water intake point [2]. That being so, not all contaminants are covered under the Act, therefore the risk of contamination cannot be totally eradicated. A fact more so true in this era of climatological and morphological changes, where rivers are more susceptible to contamination [2].